2010
DOI: 10.3109/08958378.2010.497818
|View full text |Cite
|
Sign up to set email alerts
|

The pathological response and fate in the lung and pleura of chrysotile in combination with fine particles compared to amosite asbestos following short-term inhalation exposure: interim results

Abstract: (2010) The pathological response and fate in the lung and pleura of chrysotile in combination with fine particles compared to amosite asbestos following short-term inhalation exposure: interim results, Inhalation Toxicology, 22:11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
7
31
0
1
Order By: Relevance
“…The results from the histopathological examination of the lungs have been presented in detail in Bernstein et al (2010). These findings confirmed that animals exposed to CPP produced no sign of pulmonary inflammation, aside from a macrophage response, at any time point.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…The results from the histopathological examination of the lungs have been presented in detail in Bernstein et al (2010). These findings confirmed that animals exposed to CPP produced no sign of pulmonary inflammation, aside from a macrophage response, at any time point.…”
Section: Resultssupporting
confidence: 61%
“…The bivariate length and diameter size distributions of the CSP aerosol and the amosite asbestos aerosol have been presented in Bernstein et al (2010).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations